A CDIO FRAMEWORK FOR A DIPLOMA IN CIVIL ENGINEERING PROGRAM IN MALAYSIA - Fei Ha Chiew; Nurjuhanah Juhari; Che Maznah Mat Isa, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The CDIO framework for Diploma in Civil Engineering at Universiti Teknologi MARA is designed by integrating the "Design-Implement Experiences” approach to create a dynamic, hands-on learning environment. The purpose of this paper is to examine the implementation and effectiveness of the "Design-Implement Experiences" approach within the CDIO framework in the Civil Engineering Design Project. A qualitative method by analyzing documents related to the CDIO framework for the diploma program focusing on the capstone project is conducted. The CDIO framework allows students to develop their knowledge and skills progressively from lower to higher semesters. A capstone project is introduced in the final year, where students apply the skills and knowledge learned from the previous semesters to complete a project incorporating design of reinforced concrete elements, project scheduling, structural modelling and project costing using CDIO approach. The average students’ attainment for problem solving, investigation and communication learning outcomes are 77%, 62% and 71% respectively. On average, students’ attainments for all learning outcomes meet the minimum threshold of 50%, demonstrating their ability to conduct necessary investigations, develop solutions that ensure construction feasibility, sustainability, and cost-effective design, and effectively present their findings both orally and in writing. The CDIO implementation promotes a student-centred learning approach. Future enhancements are encouraged to include sustainability and smart building features. The CDIO approach underscores the practical application of theoretical knowledge, equipping students with the skills necessary for real-world engineering tasks.